1988
DOI: 10.1366/0003702884427933
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Infrared Pharmaceutical Analysis of Two Choline Compounds by Flow Injection Analysis Using the CIRCLE Cell

Abstract: The advent of the cylindrical internal reflectance (CIRCLE) cell has solved the difficult problem of quantitation of solutes in aqueous solutions by infrared spectroscopy. By a combination of flow injection analysis (FIA) and Fourier transform infrared (FT-IR) spectroscopy with the CIRCLE cell, a fast, reproducible technique suited for the determination of two choline compounds of pharmaceutical interest—succinylcholine chloride and bethanechol chloride—was developed. Quantitation was carried out with the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Infrared spectrometry (IR) provides a useful way for the identification of drugs (USP XXII, 1990;Moffat, 1986;Ciurczak and Drennen, 2001;McClure, 1992;Garrigues et al, 1992;Miller et al, 1988) as well as for quantitative analysis, and the help of Fourier transform (FT-IR) permits continuous monitoring of the spectral baseline and simultaneous analysis of different components of the same sample.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared spectrometry (IR) provides a useful way for the identification of drugs (USP XXII, 1990;Moffat, 1986;Ciurczak and Drennen, 2001;McClure, 1992;Garrigues et al, 1992;Miller et al, 1988) as well as for quantitative analysis, and the help of Fourier transform (FT-IR) permits continuous monitoring of the spectral baseline and simultaneous analysis of different components of the same sample.…”
Section: Introductionmentioning
confidence: 99%
“…However, the traditional techniques employed to obtain the IR spectra, such as alkali halides disks, mulls, and thin films, are sometimes not adequate for quantitative analysis. Fourier transform (FT)-IR permits continuous monitoring of the spectral baseline and simultaneous analysis of different components of the same sample (Garrigues, Gallignani, and de la Guardia 1992;Miller, Danielson, and Katon 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Braue and Pannella (1987) have suggested that the reliable sensitivity limit in the analysis of aqueous solutions is 0.05% (w/v). Miller et al (1988) however, claimed that detection limits of 0.02% (w/v) were possible, thereby supporting the specified limits of the CIR-CLE cell. 303 Figure 2 shows the change in the MIR spectrum of the medium during the course of fermentation.…”
Section: Resultsmentioning
confidence: 76%